2018
DOI: 10.1073/pnas.1800826115
|View full text |Cite
|
Sign up to set email alerts
|

Distance-dependent defensive coloration in the poison frog Dendrobates tinctorius , Dendrobatidae

Abstract: Poison dart frogs provide classic examples of warning signals: potent toxins signaled by distinctive, conspicuous coloration. We show that, counterintuitively, the bright yellow and blue-black color of (Dendrobatidae) also provides camouflage. Through computational modeling of predator vision, and a screen-based detection experiment presenting frogs at different spatial resolutions, we demonstrate that at close range the frog is highly detectable, but from a distance the colors blend together, forming effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 65 publications
2
86
1
Order By: Relevance
“…In fact, studies within this system have even suggested that natural and sexual selection may operate on different aspects of frog coloration, as variation in male brightness, an important component of assortative mating and male–male interactions, is not visible to avian predators (Crothers & Cummings, ). Additionally, there is growing evidence that pattern traits in poison frogs may also be under selection (Barnett, Michalis, Scott‐Samuel, & Cuthill, ; Rojas & Endler, ; Wollenberg, Lötters, Mora‐Ferrer, & Veith, ). Studies of intrapopulation pattern variation in the poison frog Dendrobates tinctorius have demonstrated that certain pattern traits are correlated with movement behavior, suggesting that patterning elements may also be important in determining how aposematic organisms are perceived by predators (Rojas, Devillechabrolle, & Endler, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, studies within this system have even suggested that natural and sexual selection may operate on different aspects of frog coloration, as variation in male brightness, an important component of assortative mating and male–male interactions, is not visible to avian predators (Crothers & Cummings, ). Additionally, there is growing evidence that pattern traits in poison frogs may also be under selection (Barnett, Michalis, Scott‐Samuel, & Cuthill, ; Rojas & Endler, ; Wollenberg, Lötters, Mora‐Ferrer, & Veith, ). Studies of intrapopulation pattern variation in the poison frog Dendrobates tinctorius have demonstrated that certain pattern traits are correlated with movement behavior, suggesting that patterning elements may also be important in determining how aposematic organisms are perceived by predators (Rojas, Devillechabrolle, & Endler, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of intrapopulation pattern variation in the poison frog Dendrobates tinctorius have demonstrated that certain pattern traits are correlated with movement behavior, suggesting that patterning elements may also be important in determining how aposematic organisms are perceived by predators (Rojas, Devillechabrolle, & Endler, ). In fact, recent work in D. tinctorius indicates that pattern and color function as an aposematic signal to predators at close range, but are perceived as cryptic when viewed from longer distances (Barnett et al, ). Future work on phenotypic diversity in Malagasy poison frogs should draw on this body of literature and consider the relative roles of natural and sexual selection in shaping phenotypes, as well as the relative contributions of color and pattern to predator avoidance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, that match need only be accurate at the spatial frequency the viewer is sampling at; in other words, as limited by their visual acuity (Caves, Brandley & Johnsen, ). This allows the same pattern to function as camouflage at a distance, but a signal when the intended viewer is close (Endler, , ; Merilaita & Tullberg, ; Bohlin, Tullberg & Merilaita, ; Barnett & Cuthill, ; Barnett, Scott‐Samuel & Cuthill, ; Barnett et al ., ,b, ,b; Barnett, Cuthill & Scott‐Samuel, , ).…”
Section: Exploiting Receiver Psychologymentioning
confidence: 99%
“…If the background has an oriented texture, such as the vertical grain of bark on trees such as oak, then a background‐matching animal has to orient such that its texture matches (Sargent, ; Kang et al ., , ; Barnett et al ., ,b, ,b). This demands the ability to detect the background texture, not necessarily visually because tactile cues may suffice, and orient appropriately.…”
Section: Constraints On Camouflagementioning
confidence: 99%